Process of Institutionalization of Azerbaijan-Israeli Relations - E A Yakimova (Vestnik RUDN International Relations, 2014)
The article dwells upon the process of formation and work peculiarities of the key structures of the Azerbaijani-Israeli cooperation. The author pinpoints achievements in the institutionalization of economic contacts, the main of which is the creation of a bilateral chamber of commerce. However the interaction potential is not fully exploited due to the absence of the Azerbaijani embassy in Israel.